Analysis of the environmental impact of energy consumption in the production of bitcoin worldwide. - Apraez Muñoz, José Julián
The progressive development of technology in different areas of human knowledge has caused a series of changes in different components of the biosphere and of today's society; One of the most recent is the transition from physical money to virtual money, especially with the creation of cryptocurrencies such as bitcoin, as an economic alternative to develop transactions for the purchase and sale of goods or services. This type of process generates large electrical energy consumption, since blockchain technology is based on the solution of complex cryptographic problems to validate transactions, involving thousands of computers attached to the network. In this sense, this research analyzed the different countries that produce bitcoin and the energy sources that are used for the production of electrical energy, the environmental impacts of mining, and the alternative energy sources that have been chosen by different producers. For this, a deep bibliographic analysis was started through the use of bibliographic references and following the methodological strategy proposed by Reyes (2019), based on 5 moments for the development of research. As a result, it was obtained that, indeed, the production of bitcoin generates a serious environmental impact with a carbon footprint of 39.67 megatons of CO2 that are emitted into the atmosphere, product of the 50.88 TWh of annual electrical energy consumption.